Analisis Perhitungan Harga Pokok Produksi Dalam Penetapan Harga Jual Dengan Menggunakan Metode Full Costing Pada Usaha Meubel Kasih Kabupaten Kupang - Kaho, Yesti (Bisman - Jurnal Bisnis & Manajemen, 2019)
ABSTRACT The title of the research is “ the Analysis of Production Base Price Calculation in Determining the Selling Price by Using Full Costing Method in Kasih Furniture Business Kupang District”. The problem was how production base price calculation in determining the selling price by using Full Costing method in Kasih furniture business Kupang district. The aim of the research was to know production base price calculation in determining the selling price by using Full Costing method in Kasih furniture business Kupang district. The data analysis method used quantitative analysis. Quantitative analysis technique is the cost data that obtained from Kasih furniture business that overall detailed and formulated using full costing method. The difference of calculation will be analyzed and will be recommended to the company, the selected method will be the basic in determining the production base price and selling price. The calculation result showed that there was the significant difference between the calculations of company method and full costing method. The production base cost that calculated for 5 years according to the company was Rp. 560.298.750,- whereas the production base price according to the full costing was Rp. 634.628.750,-. .Furthermore the determination of company selling price for 5 years was Rp. 1.896.158,-, whereas the selling price according to full costing was Rp. 2.239.954,-, the selling price difference was Rp.343.796. So that the selling price determination must be done correctly because the very high selling price will make the product less competitive, whereas the very low selling price will make the loss of the company